Analisis Kesesuaian Lahan Kawasan Lahan Basah (Wetland) untuk Perencanaan Tata Guna Lahan Berkelanjutan di Kabupaten Tulang Bawang - Dwi Bayu Prasetya; Hediyati Anisia (Journal of Science and Applicative Technology, 2021)
The wetland area in Tulang Bawang Regency is a stretch of swamps that has an important value ecologically and hydrologically and has economic value. However, currently, the area's condition has begun to change its function to agricultural land, resulting in damage to the habitat and function of swamps, causing a decrease in biological resources such as fish and bird populations. The use of wetlands must be carefully planned and designed with land use principles with a sustainable perspective. The aim of this research is; 1.) Identifying the potential for hydrology, potential land use, and the condition of biodiversity in the Wetland area; 2) Formulating alternative land suitability in the wetland area planning in Tulang Bawang Regency by taking into account biophysical factors and area functions. This research's approach method is spatial pattern analysis, which is to study the patterns, shapes, and distribution of phenomena on the earth's surface. In addition, understand the meaning of these patterns and use them in sustainable land use planning. Based on the results of land suitability analysis for wetland planning in Tulang Bawang Regency, it can be concluded that this area is classified as very suitable (S1) with a score of 93.33. For the development of wetlands through nature conservation and cultural heritage of the Tulang Bawang community as objects and the main attraction of this area.